Investigations on the evolution of subsistence economy in the Qazvin Plain (Iran) from the Neolithic to the Iron Age - Mashkour, M.
Analysis of zooarchaeological data from three prehistoric sites on the Iranian plateau presents new details of economic strategies in this little-known region.